Preventing cognitive decline and dementia from cerebral small vessel disease: The LACI-1 Trial. Protocol and statistical analysis plan of a phase IIa dose escalation trial testing tolerability, safety and effect on intermediary endpoints of isosorbide mononitrate and cilostazol, separately and in combination. Issue 5 (July 2018) - Blair, Gordon W; Appleton, Jason P; Law, Zhe Kang; Doubal, Fergus; Flaherty, Katie; Dooley, Richard; Shuler, Kirsten; Richardson, Carla; Hamilton, Iona; Shi, Yulu; Stringer, Michael; Boyd, Julia; et al.
Rationale: The pathophysiology of most lacunar stroke, a form of small vessel disease, is thought to differ from large artery atherothrombo- or cardio-embolic stroke. Licensed drugs, isosorbide mononitrate and cilostazol, have promising mechanisms of action to support their testing to prevent stroke recurrence, cognitive impairment, or radiological progression after lacunar stroke. Aim: LACI-1 will assess the tolerability, safety, and efficacy, by dose, of isosorbide mononitrate and cilostazol, alone and in combination, in patients with ischemic lacunar stroke. Sample size: A sample of 60 provides 80+% power (significance 0.05) to detect a difference of 35% (90% versus 55%) between those reaching target dose on one versus both drugs. Methods and design: LACI-1 is a phase IIa partial factorial, dose-escalation, prospective, randomized, open label, blinded endpoint trial. Participants are randomized to isosorbide mononitrate and/or cilostazol for 11 weeks with dose escalation to target as tolerated in two centers (Edinburgh, Nottingham). At three visits, tolerability, safety, blood pressure, pulse wave velocity, and platelet function are assessed, plus magnetic resonance imaging to assess cerebrovascular reactivity in a subgroup. Study outcomes: Primary: proportion of patients completing study achieving target maximum dose. Secondary: symptoms whilst taking medications; safety (hemorrhage, recurrent vascular events, falls); blood pressure, platelet function, arterial stiffness, and cerebrovascular reactivity. Discussion: This study will inform the design of a larger phase III trial of isosorbide mononitrate and cilostazol in lacunar stroke, whilst providing data on the drugs' effects on vascular and platelet function. Trial registration: ISRCTN (ISRCTN12580546) and EudraCT (2015-001953-33).